EVALUASI BAHAN AJAR SENI RUPA DALAM BUKU SENI BUDAYA SEKOLAH MENENGAH PERTAMA - Tangsi, Tangsi; Salam, Sofyan; Husain, Muh. Saleh (Nuansa Journal of Arts and Design, 2025)
This study aims to determine: (1) the accuracy of the concept of art teaching materials in the Cultural Arts book for Junior High Schools, (2) the accuracy of the pictures to explain the concept of art teaching materials in the Cultural Arts book for Junior High Schools. The focus of the study is the accuracy of the concepts and the accuracy of the pictures of art teaching materials in the Cultural Arts book for Junior High Schools. The subject of the research was the Cultural Arts book for Junior High Schools, which was published by the Ministry of National Education, Revised Edition, 2017. Data collection techniques used were observation, FGD, and documentation. The data analysis technique used is an interactive analysis model. The results showed that there were some misconceptions in art teaching materials in the Cultural Arts Book for Junior High Schools, including ambiguous definitions, incomplete material and incompatible with fine arts theory, causing confusion for students. In addition, some of the images used to clarify the concept are incorrect, not even in accordance with the theme to be explained. As a result, the image does not function as an explanatory concept / material, but instead instead obscures the concept